Mechanisms of charge accumulation of the electrochemical system LaMnO3 / AC - Kolkovska, H.M.; Rachiy, B.I.; Kolkovskyi, P.I.; Yaremiy, I.P.; Ivanichok, N.Ya.; Lisovskiy, R.P.; Ilnytskyi, N.R. (Physics and Chemistry of Solid State, 2021)
In this work, the electrochemical behavior of LaMnO3 perovskite material and nanoporous carbon material in an aqueous solution of lithium sulfate are studied. The regularities of the expediency of the joint functioning of these materials as electrodes for a hybrid electrochemical capacitor are determined. It was found that the value of the specific capacity of the investigated electrochemical system of LaMnO3 / electrolyte / AC is 52 F/g during the discharge of the system to 1 V and the value of specific energy is 112.1 J /g at a discharge current of 1 mA.